Understanding Discordant Board Outcomes - Sherilyn W. Driscoll; Mikaela M. Raddatz; Susan Apkon; Gerard E. Francisco; Christopher Garrison; Carolyn L. Kinney; Vu Q.C. Nguyen; David W. Pruitt (American Journal of Physical Medicine & Rehabilitation, 2026)
It is unexpected when initial certification examinees pass the American Board of Physical Medicine and Rehabilitation (ABPMR) Part I Examination with a top score and subsequently fail the Part II Examination. This study aims to determine individual and residency program factors associated with this outcome. A retrospective, observational review of ABPMR data between 1999 and 2025 identified 161 individuals (1.6% of all examinees) who passed Part I with top quartile performance but subsequently failed one or more attempt at Part II. Multinomial logistic regression models demonstrated a lower odds ratio for Part II failure among female physicians (OR=0.60, P =0.016) and those enrolled in fellowship training (OR=0.53, P =0.006). A higher odds ratio was found for physicians aged >40 years (OR=3.80, P